(untitled) (Proceedings of the International Conference on Social Sciences, 2018)
The current century can be easily marked by dichotomies where on the one hand humanity is experiencing dense connectivity through advance technology and sweeping waves of globalization and on the other feeling isolated and alone at the individual level. Over emphasis on science and technology in the society as the panacea for all the problems have not only mitigated the image of the social sciences but also invited multiple troubles like terrorism, violence, intolerance, environmental degradation in an unprecedented manner. The subservient treatment of social sciences is diminishing the concern for sustaining the welfare of human being and environment through constructive and meaningful participation. With this background, this paper is attempting at the theoretical level with slight empirical evidences to inter relate social sciences for creating peaceful world. In order to vindicate the objective, data was collected from the secondary level students and pre-service teachers to know their perception for the social sciences as to what extent they are interested in pursuing for social sciences at the higher level. The paper concludes by evolving the framework where social sciences will be interlinked with the goal of creating the peaceful world.